Reconciling opposing theories of unemployment - Janse van Rensburg, Caro C (My University, 2021)
The economic contributions of Marx and Friedman would traditionally be considered in opposition to one another. Friedman (1962) himself contributed to this view by arguing against the views of Marx in his book, Capitalism and Freedom. He advocates for a free market system, whilst Marx advocated a complete transformation of the market, to deal with its inherent failings. Despite their differences, as will be discussed in greater detail below, both Friedman (1968) and Marx (2015) [1867] argue that there would always be some level of unemployment in the long run. They both explain structural unemployment as being intrinsic to the capitalist system, with its level being determined by social institutions and their actions. They come to this conclusion using very different routes, however. Marx’s analysis presumes that labour has little to no power in deciding the level of employment and wages. There is constantly a class conflict, through which labour attempts to secure a more favourable position; but, it is ultimately the accumulation of capital that determines the size of the industrial reserve army. The implication of this is that labour demand, and not supply, determines unemployment. This approach makes it clear that unemployment, from the perspective of Marx, is involuntary. On the other hand, Friedman assumes that supply and demand of labour are relatively on equal footing and therefore one can assume that Friedman’s analysis rejects the concept of involuntary unemployment. Voluntary unemployment will be discussed further in section 6 below. Neither Marx nor Friedman intended to develop a theory of unemployment, but they both used their understanding of unemployment to explain other aspects of economics. As a result, they ended up focusing their explanations on different dynamics of unemployment. Marx (2015) [1867] intended to show how capital accumulation functions in a capitalist system, and in order to do that, he explains how unemployment is a necessary component of capital accumulation. Friedman (1968) intended to show the limitations of monetary policy and needed to develop a theory of unemployment as a structural phenomenon in order to oppose the Phillips curve, which dominated monetary theory at the time. My aim is to find the commonalities and differences between the two approaches and to establish whether or not a more holistic understanding of long-run unemployment can be attained. Very little attempt has been made to reconcile the works of Marx and Friedman, presumably because of the view that they are in opposition to each other. This view is not unfounded, but I will show in this essay that, in the case of their understanding of structural unemployment, there is much that they had in common. An exception in the literature is Pollin (1999) who argues that the natural rate of unemployment (NRU) is determined through class struggle and is, therefore, a concept rather similar to the notion of an industrial reserve army. Pollin’s contribution is limited to this finding, and he does not go further to attempt to analyse and compare other aspects of the NRU and industrial reserve army. Stockhammer (2008) also shows how the reserve army of labour can be the theoretical foundation for a NAIRU (non-accelerating inflation rate of unemployment) model. The notion of a reserve army can at least, to some extent, be used to develop a NAIRU model similar to those created with the NRU as its theoretical foundation. Stockhammer does not, however, develop the link between the reserve army and the NRU, and simply uses these two theories to develop two distinct NAIRU models. In this essay, I make that theoretical link and show the ways in which the models can be reconciled, and the ways in which they cannot. It may at first seem counterintuitive to attempt this reconciliation, given their opposing political stances, but I would argue that it is exactly because of their differences that it is so interesting that they came to such a similar understanding of unemployment in the long run. This reconciliation could be particularly useful in understanding the many complexities of unemployment, which remains a pervasive global challenge. In this essay, I will discuss these two theories of unemployment. I start by explaining the natural rate of unemployment (NRU) that was conceived by Friedman and Phelps, after which Marx’s reserve army of labour will be discussed. Thereafter, I will attempt to reconcile the theories, which will include a discussion of incommensurability and voluntary unemployment. I conclude with an example of how the reserve army of labour can be employed to understand the limitations of monetary policy in the vein that Friedman originally intended for the NRU
A research report submitted in partial fulfilment of the degree of Master of Commerce (Economics/Economic Science) in the School of Economic and Business Sciences, University of the Witwatersrand, 2021